Optimizing daylight for residential buildings in Depok City, Jakarta - Prasetio Wibowo, Adhie (2015)
The issue of energy-saving buildings and energy efficiency is not really new and are closely associated with natural lighting factors especially in housing in Indonesia. To save electrical energy consumption of the lighting, the use of lighting by sunlight is constantly being developed for housing, such as in dense residential areas like in Depok. Architects play a very important role to help reduce the use of energy derived from fossil energy into a green design approach by optimizing natural lighting from the sun. Therefore, the directions of light along with the effects of reflection or refraction also need to be arranged accordingly to create the visual comfort of the space. The method used was by experiential and data collection on samples of two housing models facing north and south which are commonly found in dense residential area in 1 akarta strongly supported by literature studies and modelling by Ecotect simulation